Sekolah Kebangsaan Alai online booking system (SKAOBS) - Hazwani Liana, Abbas (2012)
Sekolah Kebangsaa Alai(SKA)is a primary school that is provide booking management for teaching equipment that available in school library’s screening room.It manages the operational of the reservation in matter of booking items. There are several problems identified when using the manual system.The process is conducted in manually.Problem occurs when there is redundancy of reservation.Person in charge hard to find available item where they need to check on self before approve the reservation.Data is also not being kept in the secure location.Information lost is common by using manual system.For the solution of the problems,SKA Online Booking System is developed to manage the operational of the reservation in matter of booking process and item management.SKAOBS is a web-based application system.The significant of the system allows the admin,staff,normal user and driver to check the availability of items directly.Data will be stored in a database. To develop this system, Prototype model had been chosen as a methodology.Hopefully this system can be really helpful and provide services and satisfaction to the user.